7-4=4y*(8-6)-64

Simple and best practice solution for 7-4=4y*(8-6)-64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-4=4y*(8-6)-64 equation:



7-4=4y(8-6)-64
We move all terms to the left:
7-4-(4y(8-6)-64)=0
We add all the numbers together, and all the variables
-(4y2-64)+7-4=0
We add all the numbers together, and all the variables
-(4y2-64)+3=0
We get rid of parentheses
-4y2+64+3=0
We add all the numbers together, and all the variables
-4y^2+67=0
a = -4; b = 0; c = +67;
Δ = b2-4ac
Δ = 02-4·(-4)·67
Δ = 1072
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1072}=\sqrt{16*67}=\sqrt{16}*\sqrt{67}=4\sqrt{67}$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-4\sqrt{67}}{2*-4}=\frac{0-4\sqrt{67}}{-8} =-\frac{4\sqrt{67}}{-8} =-\frac{\sqrt{67}}{-2} $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+4\sqrt{67}}{2*-4}=\frac{0+4\sqrt{67}}{-8} =\frac{4\sqrt{67}}{-8} =\frac{\sqrt{67}}{-2} $

See similar equations:

| 10x+18=64x | | 7(2l+10)=196 | | -1/3(f+8)=13 | | 3(1+15n)−17n=−361 | | 12x-5=8-25 | | 5u=3+8u | | 4(3x-1)+5=61 | | 4(3n+5)=60 | | 1/2+x=8/15 | | 1+2(q-2)=4(q+2)-5 | | 7*b/4=-49 | | -5(n+8)=-10 | | 31=y/4+8 | | y+0,2(3-2y)=0,5(5y+2)-8 | | Y=15.5x+10 | | -12(4-x)=108 | | 16+y=37 | | 9.7t+3.4=9.5t | | 4x+20=7x+56 | | 3x+-18=20 | | n^2+7n=60 | | 9(-2x-5)=16 | | 1/3+2/3(q-2)=4/3(q=2)-5/3 | | 4x-x-x=18 | | -8(7x-3)=-88 | | -14.4c+3.92=-13.88-15.4c | | 4d+3=(2d-7) | | 40x=20x | | 3a–9+7=5a | | 4h=8+6h | | 10(6x-3)=90 | | 10x-2.6666666667-4x=6x |

Equations solver categories